PELATIHAN PENCEGAHAN DAN PERTOLONGAN JATUH PADA LANSIA BAGI KELUARGA DI WILAYAH KERJA PUSKESMAS II DENPASAR TIMUR - Utami, P.A.S.; Kamayani, M.O.A.; Puspita, L.M.; Raya, N.A.J. (Buletin Udayana Mengabdi, 2018)
Aging in muskuloskletal system resulted the elderly prone to falling. Fall can result in physical injury, trouble walking or disability. Knowledge of the falls prevention need to be owned by a family to care the elderly. The aim of this community service is to increase the ability of families and aid in the prevention of falls in the elderly in Puskesmas II East Denpasar. Participants involved 45 families who have elderly. The method used to provide education and demonstrations on how prevention and relief falls in the elderly. The result is the increase amounted to 31.1% of family knowledge which 88.9% had good knowledge after obtaining the training. Statistical test results obtained with the Wilcoxon test p-value=0.000<0.05 which means that there is the effect of health training to the families knowledge about the prevention and relief of elderly falls. Prevention and rescue risk of falls in the elderly which done properly by the family can prevent complications from a fall.